The Impact of Paid Maternity Leave on the Mental and Physical Health of Mothers and Children: A Review of the Literature and Policy Implications. Issue 2 (March 2020) - Van Niel, Maureen Sayres; Bhatia, Richa; Riano, Nicholas S.; de Faria, Ludmila; Catapano-Friedman, Lisa; Ravven, Simha; Weissman, Barbara; Nzodom, Carine; Alexander, Amy; Budde, Kristin; Mangurian, Christina
Abstract : Abstract: For decades, national paid maternity leave policies of 12 weeks or more have been established in every industrialized country except the United States. Despite women representing 47% of the current U.S. labor force, only 16% of all employed American workers have access to paid parental leave through their workplace. As many as 23% of employed mothers return to work within ten days of giving birth, because of their inability to pay living expenses without income. We reviewed recent studies on the possible effects of paid maternity leave on the mental and physical health of mothers and children. We found that paid maternity leave is associated with beneficial effects on (1) the mental health of mothers and children, including a decrease in postpartum maternal depression and intimate partner violence, and improved infant attachment and child development, (2) the physical health of mothers and children, including a decrease in infant mortality and in mother and infant rehospitalizations, and an increase in pediatric visit attendance and timely administration of infant immunizations, and (3) breastfeeding, with an increase in its initiation and duration. Given the substantial mental and physical health benefits associated with paid leave, as well as favorable results from studies on its economic impact, the United States is facing a clear, evidence-based mandate to create a national paid maternity leave policy. We recommend a national paid maternity leave policy of at least 12 weeks.